The Mediating Role of Organizational Commitment on the Relationship Between Emotional Labor and Work Engagement of Teachers - Sezen-Gultekin, Gozde; Bayrakcı, Mustafa; Limon, İbrahim (Frontiers in Psychology, 2021)
This study aims to investigate the mediating role of teachers’ organizational commitment (OC) on the relationship between their emotional labor (EL) and work engagement (WE). The study employed a cross-sectional design. The sample of the study consisted of the teachers working in Sakarya province of Turkey. They participated in the study voluntarily and responded scale items online. The findings showed that teachers’ perceptions of EL, OC and WE is relatively high. Also, there are statistically significant and positive correlations among variables. On the other hand, the findings confirmed the hypotheses. Teachers’ EL predicts their OC and WE. Additionally, OC predicts WE and plays a mediating role on the relationship between EL and WE. Based on the findings some suggestions were made.